Kemampuan Pemecahan Masalah Matematika Siswa yang Diajar dengan Menerapkan Missouri Mathematics Project - Nurjannah; Djadir; Awi (Issues in Mathematics Education (IMED), 2017)
This research was pre experimental research. The experimental design used was One-Group Pretest-Posttest Design which aims to describe and to know the problem solving ability of students of class VIII 3 was taught by applying the model of Missouri Mathematics Project of grade VIII 3. The population was the students of class VIII and the sample was class VIII 3 consisting of 30 students as an experimental class. Based on the results of research and discussion, students were able to solve mathematical problems based on indicators of mathematical problem solving ability. The result of hypothesis test shows: 1)The mean posttest score of the students meets the determined KKM value that is greater equal to 78. This means that the postest average value is significantly greater than 77.9; 2)The average normalized gain value exceeds the medium category. This means that the average value of the gain normalized significantly more than 0.29; and 3)The posttest score obtained by the students has been completed by classical test based on the proportion test. This means that the classical mastery of students' mathematical problem solving abilities after the applied learning model of the Missouri Mathematics Project is significantly more than 0.849.